Water Quality Measurement based on Internet of Thing - Fajri, Misbahul; Jumaryadi, Yuwan; Parlina, Anne (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2025)
Good water quality is crucial for living things, including temperature, pH, and TDS, which are constantly changing due to various factors. These three water parameters are crucial for maintaining water quality within a certain threshold to ensure that an ecosystem meets specified standards. Measuring water quality is essential to anticipate these changes as desired. Internet of Things (IoT) technology allows continuous monitoring of water parameters at any time and can be accessed anywhere with a network connection via computer or smartphone. In this proposed research, an IoT-based system based on ESPHome will be developed for water quality measurement in aquarium water and its ecosystem. The proposed research detects, records, and displays water pH and TDS parameters, including temperature, using an ESP8266 microcontroller. The system utilizes sensors to detect water parameters; the system utilizes an ESP8266 microcontroller and a WiFi connection that sends data to a cloud-based server with a Homeassistant dashboard. The research results are well-functioning in both hardware and software and are easily accessible.